2013
DOI: 10.7575/aiac.ijalel.v.2n.3p.129
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion in News Articles: A Discourse Analysis Approach

Abstract: The article explores the use of technology in EFL classes to promote communicative competence. It elucidates communicative competence and explicates obstructions in communicative tasks. Moreover, it interprets the use of technology in fostering and supporting the development of communicative competence and explains how it is pragmatic in maintaining learners' level of motivation and interest in learning a foreign language. The present article identifies the significance and use of mobile phone, camera, compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, both substitution and ellipsis are found to be absent within the three selected news editorials. Since the utilization of both substitution and ellipsis is implying a rigid division into watertight compartments (Halliday & Hasan, 1976), they are mostly found academic writings (Abdul Rahman, 2013;Leupold, Klinger & Jarren, 2018;Michael et al, 2013;Richardson, 2017). Studies such as conducted by Michael et al (2013) and Thipwatee & Lerdpisalwong (2021) found out that both substitution and ellipsis are absent in the news editorials they analyzed.…”
Section: Synonymymentioning
confidence: 99%
See 3 more Smart Citations
“…However, both substitution and ellipsis are found to be absent within the three selected news editorials. Since the utilization of both substitution and ellipsis is implying a rigid division into watertight compartments (Halliday & Hasan, 1976), they are mostly found academic writings (Abdul Rahman, 2013;Leupold, Klinger & Jarren, 2018;Michael et al, 2013;Richardson, 2017). Studies such as conducted by Michael et al (2013) and Thipwatee & Lerdpisalwong (2021) found out that both substitution and ellipsis are absent in the news editorials they analyzed.…”
Section: Synonymymentioning
confidence: 99%
“…Many discourse analysts evaluate the broader discourse context in order to comprehend how it influences the sentence's meaning either in written or oral communication. Thus, by engaging in DA, it assists scholars in uncovering the motive behind any kind of text by enabling them to evaluate an issue from a higher perspective (Martin, 2005;Michael et al, 2013;Sitio, 2022;Tanskanen, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies of cohesion in Indonesian language has been explained in the literature review. The results of the cohesion studies in English including the works from Hameed (2008), Michael et al (2013), andBahazig (2016).…”
Section: International Journal Of Social Service and Researchmentioning
confidence: 99%